Clinicopathological significance of TM4SF5 expression in human hepatocellular carcinoma tissues - Xu, Baojin (Oncol Lett, 2019)
Hepatocellular carcinoma (HCC) is a major cause of cancer-related mortality. Recent studies have indicated that transmembrane 4 L six family member 5 (TM4SF5) serves a vital role in tumor progression and metastasis in human cell lines and mouse models. However, little is known about the association between TM4SF5 expression and clinicopathological factors. The aim of the current study was to investigate this association and evaluate overall survival (OS) of patients. Immunohistochemistry and clinical record analysis revealed that TM4SF5 expression was significantly downregulated in HCC tissues. In addition, TM4SF5 expression was significantly associated with tumor size, vascular invasion, tumor differentiation, and tumor-node-metastasis stage. The survival analysis also demonstrated that low TM4SF5 expression resulted in shorter OS. In conclusion, the association between TM4SF5 expression and clinicopathologic factors was established, and prognostic significance of TM4SF5 as a potential biomarker was evaluated using human HCC formalin-fixed paraffin-embedded tissue samples. The results of the present study demonstrated that low TM4SF5 expression was associated with tumor malignant progression and may be a good prognostic biomarker for OS in HCC.